Optimal arrangements of scanning heads for self-calibration of angle encoders. (15th September 2017) - Jiao, Yang; Dong, Zeguang; Ding, Ye; Liu, Pinkuan
Abstract: The calibration of the angle encoder is necessary to improve the accuracy of angle measurement in precision rotating devices. Due to the characteristics of in situ calibration of encoders, self-calibration methods depending on special arrangements of multiple scanning heads have been widely used. Conventional works usually arrange the scanning heads in a regularly distributed way, generally involving too many scanning heads, especially when more high order Fourier components of the encoder error are calibrated. This paper presents an optimization-based arrangement method for self-calibration of angle encoders. Fourier approaches are used to determine the error of encoder from the angle differences measured between scanning heads. The relations between detectable Fourier components of the error and angular intervals of the heads are obtained from the properties of transfer functions. The optimal arrangements for two and three scanning heads, including the adjustment tolerances of the heads with the range of tested Fourier orders, are presented. The results of simulations and experiments demonstrate that the proposed optimal schemes can realize the same performance of calibration but with fewer scanning heads, compared to the conventional methods.